Individual Health Budgets in Mental Health: Results of Its Implementation in the Friuli Venezia Giulia Region, Italy - Fontecedro, Elisa; Furlan, Morena; Tossut, Davide; Pascolo-Fabrici, Elisabetta; Balestrieri, Matteo; Salvador-Carulla, Luis; D’Avanzo, Barbara; Castelpietra, Giulio (International journal of environmental research and public health, 2020)
Background: Individual Health Budget (IHB) is an intervention for recovery in mental health services, providing personalized care for subjects with severe disorders and complex needs. Little is known on its effectiveness and on the criteria for its delivery. Methods: A total of 67 IHB beneficiaries and 61 comparators were recruited among service users of the Mental Health Department of the Trieste Healthcare Agency, Italy. Data included sociodemographic and clinical variables, type of IHB, and Health of the Nation Outcome Scale (HoNOS) scores. Results: A comparison between groups showed significant differences in several socioeconomic and clinical characteristics. Multivariate logistic regression showed that IHB was positively associated to the 20–49 age group, single status, unemployment, low family support, cohabitation with relatives or friends, diagnosis of personality disorder, and a higher number of hospitalizations. The IHB group was at a higher risk of severe problems related to aggressive or agitated behaviors (OR = 1.4), hallucinations and delusions (OR = 1.5), and impairment in everyday life activities (OR = 2.1). Conclusions: IHB was used in patients with severe clinical and social problems. More resources, however, may be aimed at the working and social axes. More research is needed to better assess clinical and social outcomes of IHB and to adjust their intensity in a longitudinal perspective in order to enhance cost-effectiveness.